Reduction in peripheral blood leukocyte heat shock proteins 27 and 70 expression in chronic obstructive pulmonary disease - Rumora, Lada (Array, 2008)
Summary: Chronic obstructive pulmonary disease (COPD) is characterized by chronic local and systemic inflammation, and increased oxidative stress. Changes in peripheral blood leukocyte counts or in the fractions of leukocyte subsets might be implicated in the development of this disease. In this study, increased monocyte fraction was observed in COPD non-smokers. In light COPD smokers, the fraction of neutrophils was significantly increased along with significantly decreased lymphocyte fraction and lung function parameters. Heat shock proteins (Hsps) could stimulate antioxidant defence of cells by decreasing intracellular levels of reactive oxygen particles (ROS) and by neutralizing toxic effects of oxidized proteins. This study showed that the expression of Hsps in leukocytes was influenced by health and smoking status. Hsp70 and Hsp27 were significantly decreased in COPD ex-smokers and healthy smokers, but the most striking suppression in Hsps expression was detected in COPD smokers. It is suggested that this decline in Hsps intracellular levels could be implicated in the pathogenesis of COPD